Kapag lumaban ang api ([s.l.] Aquarius Records)
Too much injustice and abuse led to the lost of many lives not to mention the paid support of the police authority that drove Mr. Julio Magsalin (Fernando Poe Jr.) to jail. With clenched fist, he has to come back and fight not only for his family but also for the oppressed and the welfare of their well-loved Samonte Sugar Estate.
VCD
Music : Ernani Cuenco, executive producer : Emilia Santos-Blas, directed by Ronwaldo Reyes
Fernando Poe, Jr., Miguel Rodriguez, Lorraine Schuck
Keywords: Action--Feature.; Drama--Feature.